Designing Reading Materials for the Faculty of Social and Political Sciences at UIN Syarif Hidayatullah Jakarta - Devi Yusnita (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2015)
This research is aimed to design reading materials for the Faculty of Social and Political Sciences, UIN Syarif HIdayatullah Jakarta, due to the absence of such specific materials in the market. To produce satisfactory teaching materials, the researcher did some steps i.e. doing needs analysis, reviewing the principles of materials design and reading strategies, designing course framework, designing syllabus, designing the reading materials, and implementing the sample lessons. The needs analysis was intended to find out what the students needed and to find out the subjects the students learned from the institution in order to produce adequate reading materials. Based on the needs analysis, the researcher then identified the global aims of the course, thereby, the writer designed course framework. This course framework contained general points of reading themes and topics, information of classroom activities that followed up reading, the length of study session, the number of the course meetings, and the number of participants. The course framework became the basis to write the syllabus. Finally the syllabus became the basis for designing reading materials.